Tentatives d’accommodement et justice parallèle à Lyon dans la seconde moitié du xviiie siècle. L’enseignement des archives judiciaires - Marc Vacher (L'Atelier du CRH)
In Lyon society under the Old Regime, settling a dispute by mutual agreement through arbitration was a mechanism which contributed to creating household equilibrium. It may appear paradoxical to analyse these attempts at agreement by using judicial sources because these practices took place by definition on the margins of official justice. However, the proceedings brought to the royal courts contain cases which can enrich our understanding of this form of parallel transaction. Through an analysis of trial records, this article seeks to draw up a typology of the conflicts settled by mutual agreement, to establish a portrait of the mediators, to describe the ways in which the parties came to an agreement and the forms of agreement reached.